The effect OF Cr, Cr-N and Cr-Ox coatings on deuterium retention and penetration in zirconium alloy Zr-1Nb - Kopanetz, I.E.; Tolstolutskaya, G.D.; Nikitin, A.V.; Bilous, V.A.; Kuprin, A.S.; Ovcharenko, V.D.; Vasilenko, R.L. (Вопросы атомной науки и техники, 2015)
Depth distribution profiles of deuterium in zirconium alloy Zr-1Nb in initial state and with coatings Cr, CrN, and Cr₂O₃ after ion implantation with 15 keV/D⁺ at temperatures 350 °C to dose 1·10¹⁷ D/cm⁻² and deuterium plasma of glow discharge at room temperature are determined by the method of nuclear reactions. It is shown that in studied range of temperatures and concentrations of deuterium coatings CrN and Cr₂O₃ act as barrier and protect zirconium from interaction with hydrogen isotope. У вихідному сплаві цирконію і в сплаві з Cr-, CrN- и Cr₂O₃-покриттями методом ядерних реакцій виміряні профілі розподілу дейтерію, який імплантований з енергією 15 кеВ/D⁺ при температурі 350 °С до дози 1·10¹⁷ D/см⁻² і впроваджений при впливі плазми тліючого розряду. Показано, що в дослідженому інтервалі температур і концентрацій покриття CrN и Cr₂O₃ виступають бар'єром і захищають цирконій від взаємодії з ізотопом водню - дейтерієм. В исходном сплаве циркония и в сплаве с Cr-, CrN- и Cr₂O₃-покрытиями методом ядерных реакций измерены профили распределения дейтерия, имплантированного с энергией 15 кэВ/D⁺ при температуре 350 °С до дозы 1·10¹⁷ D/см⁻² и внедренного при воздействии плазмы тлеющего разряда. Показано, что в исследованном интервале температур и концентраций покрытия CrN и Cr₂O₃ выступают барьером и защищают цирконий от взаимодействия с изотопом водорода - дейтерием.